Clinical Observation of Low-Temperature Plasma Knife Tonsil Adenoidectomy for Pediatric Snoring and Analysis of Influencing Factors. (24th November 2022) - Guo, Li; Hu, Yirong
Abstract : Objective. To investigate the clinical efficacy of low-temperature plasma knife tonsil adenoidectomy for pediatric snoring and to analyze the factors influencing the efficacy. Methods. 90 children with snoring who were scheduled for surgical treatment in our hospital from June 2020 to December 2021 were selected as the research objects. According to the random number table method, they were divided into control group (group C) and observation group (group O), with 45 cases in each group. The children in group C were treated with power cutting system to remove adenoids combined with conventional peeling of bilateral tonsils, while the children in group O were treated with low-temperature plasma adenoidectomy combined with bilateral tonsillectomy, and both the groups received psychological care, preoperative preparation, health guidance, postoperative posture care and close monitoring of vital signs during the perioperative period. The clinical efficacy, perioperative related indexes (including operation time, intraoperative bleeding, postoperative pain time, and hospital stay) were compared between the two groups. The apnea-hypopnea index (AHI), oxygen decrement index (ODI), longest apnea time (LAT), and lowest oxygen saturation (LSaO2 ) were measured before operation and 1 week after operation to evaluate the ventilatory function of the two groups. According to the curative effect, 90 children with snoring were divided into cure + significant effective group and valid + invalid group. The general data and preoperative biochemical indexes of the two groups were collected, and logistic regression model was used to analyze the related influencing factors of the curative effect. Results. The total effective rate of group O (100.00%, 45 cases) was significantly higher than that of group C (91.11%, 41 cases) ( P < 0.05); the operative time, intraoperative bleeding, postoperative pain time, and hospitalization time of group O were shorter/less than those of group C; the AHI, ODI, and LAT of group O at 1 week after surgery were shorter/less than those of the control group; and LSaO2 was higher than that of group C. The differences were statistically significant ( P < 0.05). Univariate analysis showed that there were significant differences in age, BMI, course of disease, preoperative AHI, preoperative LsaO2, and surgical method between cure + significant effective group and valid + invalid group ( P < 0.05). Multivariate analysis showed that high BMI, high preoperative AHI, and power cutting system for adenoids combined with routine peeling of the bilateral tonsils were independent risk factors for postoperative outcome in children with obstructive sleep apnea syndrome (OSAS) ( P < 0.05).